Produção de ácido giberélico por fermentação em estado sólido empregando substratos agroindustriais - Pinheiro, Upiragibe Vinícius (2015)
The gibberellic acid (GA3) is a natural hormone found in some plants, this hormone has been used in agricultural formulations, as growth regulator, highly relevance both economic and industrial. Currently, its industrial scale production is achieved by Submerged Fermentation (SF) using the fungus Gibberella fujikuroi. The main problem in the industrial process is related to the low yield of GA3, causing the purification process presents high costs. An alternative to this process is the Solid- State Fermentation (SSF) that allows to obtain higher concentrations of this product. The greatest advantage of the SSF front SF is related to increased production of GA3 using low cost substrates such as waste and by-products of agroindustry. Given the fact that Brazil is highlighted as one of the most prosperous countries in terms of agricultural production, and the Rio Grande do Sul accounts for about 30-40% of rice and barley production in the country, this research evaluated the use of Raw Rice Bran (RRB) and Wet Brewery Waste (WBW), rice processing and brewing industry residues, as substrates for GA3 production by the fungus Gibberella fujikuroi. Two experimental designs, a linear type 2n and CCRD, both for two variables were performed. The first design evaluated, on three levels, evaluated the effect of moisture content in the range of 50 to 70%, and the composition of the medium, with RRB content ranging from 30 to 70% of the total substrate mass (RRB and WBW mass). In turn, the second planning in 5 levels, evaluated the effect of the addition of glucose, the carbon source over the range 0 to 80 g/L, and ammonium nitrate (NH4NO3), the nitrogen source, in the range 0 - 5 g/L, by making use of the best conditions of the first planning. It was found that, for seven days of fermentation, the greater yield for the first research proposed, was at the test carried out with medium composition of 30% RRB and 70% WBW and moisture content equals 70%. At the second design It was observed that the highest concentration of NH4NO3 favored the formation of GA3 by the fungus, towards intermediate value to the glucose content. Finally, investigation of the kinetic behavior showed an increase in production of GA3, with the peak on the seventh day with maximal production of 10,10 g/kg of substrate, and subsequent tendency for stabilization.